Achieving Greater Health Equity: An Opportunity for Anesthesiology. (2nd February 2022) - Diallo, Mofya S.; Tan, Jonathan M.; Heitmiller, Eugenie S.; Vetter, Thomas R.
Abstract : Anesthesiology and anesthesiologists have a tremendous opportunity and responsibility to eliminate health disparities and to achieve health equity. We thus examine health disparity and health equity through the lens of anesthesiology and the perspective of anesthesiologists. In this paper, we define health disparity and health care disparities and provide tangible, representative examples of the latter in the practice of anesthesiology. We define health equity, primarily as the desired antithesis of health disparity. Finally, we propose a framework for anesthesiologists, working toward mitigating health disparity and health care disparities, advancing health equity, and documenting improvements in health care access and health outcomes. This multilevel and interdependent framework includes the perspectives of the patient, clinician, group or department, health care system, and professional societies, including medical journals. We specifically focus on the interrelated roles of social identity and social determinants of health in health outcomes. We explore the foundational role that clinical informatics and valid data collection on race and ethnicity have in achieving health equity. Our ability to ensure patient safety by considering these additional patient-specific factors that affect clinical outcomes throughout the perioperative period could substantially reduce health disparities. Finally, we explore the role of medical journals and their editorial boards in ameliorating health disparities and advancing health equity.